Human Reliability Analysis in Acetylene Filling Operations: Risk Assessment and Mitigation Strategies - Michaela Balazikova; Zuzana Kotianova (Applied Sciences)
Human reliability is a key factor in long-term sustainability, especially for tasks that are critical to safety. It is also evident that human behavior is often the main or significant cause of system failures. Identifying human error is challenging, particularly when it comes to determining the exact moment when an error occurred that led to an accident, as errors develop over time. It is essential to understand the causes and mechanisms of human errors. This finding is not new; for over 30 years, it has been recognized that human operations in safety-critical systems are so important that they should be modeled as part of risk assessment in operation. This article discusses various HRA methodologies and argues that further research and development are necessary. An example of selected HRA techniques will be demonstrated through a case study on acetylene filling activities. When filling acetylene into pressure vessels or cylinders, it is critically important to analyze the reliability of the human factor, as this process involves handling a highly explosive gas. Irresponsibility, lack of training, or incorrect decision-making can lead to severe accidents. Any deficiencies in this process can result in not only equipment damage but also endanger the health and lives of people nearby. This case may also suggest potential improvements to existing guidelines, international standards, and regulations, which often require the consideration of a wider range of ergonomic factors in the risk assessment process.